2007
DOI: 10.1152/ajplung.00071.2006
|View full text |Cite
|
Sign up to set email alerts
|

In utero nicotine exposure alters fetal rat lung alveolar type II cell proliferation, differentiation, and metabolism

Abstract: We recently suggested that alveolar interstitial fibroblast-to-myofibroblast transdifferentiation may be a key mechanism underlying in utero nicotine-induced lung injury. However, the effects of in utero nicotine exposure on fetal alveolar type II (ATII) cells have not been fully determined. Placebo, nicotine (1 mg/kg), or nicotine (1 mg/kg) + the peroxisome proliferator-activated receptor (PPAR)-gamma agonist prostaglandin J(2) (PGJ(2), 0.3 mg/kg) was administered intraperitoneally once daily to time-mated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 33 publications
(35 reference statements)
6
68
1
1
Order By: Relevance
“…To elaborate on the mechanism of the effects of hyperoxia on lung injury and how it is mediated by RGZ, e20 fetal rat lung fibroblasts were cultured according to previously described methods (20). At 80% confluence, cells were pretreated for 1 h with either transforming growth factor (TGF)-␤1, -␤2, or -␤3 antibody (10 M, R&D System, Minneapolis, MN) or RGZ (10 M, St. Louis, MO).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elaborate on the mechanism of the effects of hyperoxia on lung injury and how it is mediated by RGZ, e20 fetal rat lung fibroblasts were cultured according to previously described methods (20). At 80% confluence, cells were pretreated for 1 h with either transforming growth factor (TGF)-␤1, -␤2, or -␤3 antibody (10 M, R&D System, Minneapolis, MN) or RGZ (10 M, St. Louis, MO).…”
Section: Animalsmentioning
confidence: 99%
“…The trafficking of neutral lipid from the circulation is mediated by the lipofibroblast phenotype (34), which is determined by the expression of peroxisome proliferator-activated receptor-␥ (PPAR-␥), which plays a critical role in normal lung development and injury/repair (30,35). Our laboratory has recently shown that administration of PPAR-␥ agonist rosiglitazone (RGZ) postnatally enhances lung maturation and can prevent hyperoxia-induced neonatal lung injury, suggesting the potential therapeutic usefulness of PPAR-␥ agonists in preventing and/or treating bronchopulmonary dysplasia (4,20,36). However, it is not known whether administration of PPAR-␥ agonists antenatally could prevent neonatal lung injury.…”
mentioning
confidence: 99%
“…In adition, rapidly dividing cells are more vulnerable to the effects of foreign substances such as nicotine [30]. Now it is more interesting to show our finding on examining testicular sections.…”
Section: Discussionmentioning
confidence: 74%
“…This is important as nicotine is genotoxic [30] and induces the release of oxidants [31]. Since rapidly dividing cells are more vulnerable to the effects of foreign substances such as nicotine [32], it is conceivable that nicotine exposure during gestation and early postnatal life via maternal milk may interfere with growth and development. This can be achieved in two ways: by having a direct effect on cells and/or by reducing the nutrient supply to the fetus during gestation and lactation.…”
Section: Nicotine Uptake and Metabolism During Pregnancymentioning
confidence: 99%
“…It has been shown that long-term nicotine exposure results in a predisposition for the induction of genetic instability [32,34,45]. Gene amplification is a hallmark of gene instability.…”
Section: Mechanisms Of Action Of Nicotinementioning
confidence: 99%